TRANSFORMASI LITERASI KEAGAMAAN MELALUI MEDIA SOSIAL DALAM PERSPEKTIF PENDIDIKAN ISLAM MODERN - Faruqi, Dwi (STKIP Pesisir Selatan, 2025)
The transformation of religious literacy through social media has become a significant phenomenon in the development of Islamic education in the digital era. Social media has reshaped how the millennial generation acquires and understands Islamic teachings, shifting from traditional patterns to more open and interactive forms of learning. This study aims to analyze the transformation of religious literacy occurring through social media and its implications for modern Islamic education. The research employed a descriptive qualitative approach with data collected through digital observation, in-depth interviews, and documentation. The results reveal that social media functions as a non-formal Islamic educational space that fosters participation, dialogue, and creativity in learning religion. However, the accessibility of information also poses challenges such as oversimplification of teachings and a crisis of religious authority. Modern Islamic education must respond to this transformation by developing digital religious literacy rooted in ethics, critical thinking, and Islamic spiritual values. In conclusion, social media holds great potential as an instrument for renewing Islamic education that is adaptive to technological change and the learning needs of the millennial generation.